Cuidémonos (2020)
CuidéMONOS is an education project, for children in rural areas of Colombia, developed along with the Asociación Primatológica Colombiana (APC). The project consists of a platform with different tools for the use of teachers in schools as well as parents at home, to help educate about the conservation of the brown spider monkey. The objective, is to manage the translation and transfer of knowledge about this species of monkey through stories, illustrations and engaging activities for children, in order to change the way the kids relate to their environment and in order to have an impact both in their homes and in their communities. This proposal is summarized in an Instagram account, so it is available for people all around the country, displaying different types of content which is aligned with the APC?s objectives and with the national Basic Standards of Education. Although the format is digital, thinking of having a greater reach especially during these times of social distancing, the platform has the option to download the files and print them at home for different acivities. The stories and characters of the project are created together with biologists and with people from specific communities, in this case with people from Bocas del Carare in the Magdalena Medio. The above, looking forward to being a solid and relevant project in the context of rural education in Colombia. Also, the characters, settings and situations are inspired by real events and people.